2006
DOI: 10.1021/ac0519007
|View full text |Cite
|
Sign up to set email alerts
|

Electron Capture Dissociation in a Digital Ion Trap Mass Spectrometer

Abstract: Electron capture dissociation was implemented in a digital ion trap without using any magnetic field to focus the electrons. Since rectangular waveforms are employed in the DIT for both trapping and dipole excitation, electrons can be injected into the trap when the electric field is constant. Following deceleration, electrons reach the precursor ion cloud. The fragment ions produced by interactions with the electron beam are subsequently analyzed by resonant ejection. [Glu(1)]-Fibrinopeptide B and substance P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 27 publications
1
67
0
Order By: Relevance
“…The analytical power of ECD in FT-ICR MS encouraged researchers to develop alternative methods for lower resolution mass spectrometers. As a result, ECD and ion-ion reaction based electron-transfer dissociation (EID) have been implemented and developed into efficient tools in linear and Paul radiofrequency ion traps [6][7][8][9][10] as well as in a digital ion trap [11]. ECD/EID implementation in radiofrequency devices that typically constitute the first stage of a hybrid mass spectrometer allows for subsequent high-resolution detection of product ions with FT-ICR, Orbitrap [12], or time-of-flight (TOF) [13] mass analyzers.…”
mentioning
confidence: 99%
“…The analytical power of ECD in FT-ICR MS encouraged researchers to develop alternative methods for lower resolution mass spectrometers. As a result, ECD and ion-ion reaction based electron-transfer dissociation (EID) have been implemented and developed into efficient tools in linear and Paul radiofrequency ion traps [6][7][8][9][10] as well as in a digital ion trap [11]. ECD/EID implementation in radiofrequency devices that typically constitute the first stage of a hybrid mass spectrometer allows for subsequent high-resolution detection of product ions with FT-ICR, Orbitrap [12], or time-of-flight (TOF) [13] mass analyzers.…”
mentioning
confidence: 99%
“…Since the electron capture process requires low energy electrons (<10 eV) and long interaction times, the application of ECD was traditionally confined to instruments that employ static electromagnetic fields that avoid energizing or heating electrons, such as Fourier transform ion cyclotron resonance (FT-ICR) MS. Recently however, the addition of magnetic fields to ion traps have allowed for ECD in such electrodynamic trapping instruments (Baba et al, 2004) and the use of ECD in a digital ion trap mass spectrometer has also been reported (Ding & Brancia, 2006). Electron transfer dissociation (ETD) is similar to ECD in that it also induces relatively nonselective cleavage of the N-C bond on a peptide's backbone producing c-and z-product ions, while maintaining phosphate groups and other potentially labile modifications (Syka et al, 2004).…”
Section: Electron Capture Dissociation (Ecd) and Electron Transfer DImentioning
confidence: 99%
“…Digital ion trap (DIT) technology was developed recently, and has been proven to have many advantages [25][26][27][28][29][30]. In DIT, a rectangular waveform is used to drive the ion trap for trapping ions; ion resonance excitation could also be realized by a rectangular waveform that produces via frequency division of the main digital rectangular waveforms, i.e., trapping waveform.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, both the digital rectangular waveform amplitude and frequency affect the ion excitation and its kinetic energy. Mass analysis in DIT is also realized by scanning the frequency of trapping waveform [26][27][28]. Our recent research results found that highly efficient CID can be realized by simply changing the duty cycle of the resonance excitation waveform and the associated frequency [29,30].…”
Section: Introductionmentioning
confidence: 99%